Studi Tentang Desain Pakaian Pengantin Suku Talang Mamak dikecamatan Rakit Kulim Kabupaten Indragiri Hulu Provinsi Riau - Jubaedah, Siti; Efi, Agusti; Yuliarma, Yuliarma (Journal of Home Economics and Tourism, 2014)
This study aimed to documentation , analyze and describe data about wedding apparel designs Talang Mamak tribe as seen from the Bride Outfits design philosophy and meaning. This research is descriptive qualitative. The location of this study in the district of Kulim Raft Indragiri Hulu in Riau Province. Â Data collection techniques using three techniques are observation, interview and documentation. The results of the study Talang Mamak tribe clothing Bridal bride and groom men wearing form perempuanya shirts, pants, and cap Salempang . Material shirts of cotton, wool, Salempang, cotton and velvet . Kundur florals and diamonds. Colors used red and black color hiasanya using woven hangings . Bride of using the short form of Kebaya , gloves , and tools Salempang andam, songket woven material , meaning the philosophy of the wedding dress is courage, sanctity became the bride dared to enter the gates of the household and cheerfulness lost all cocky arrogant, originated from the household life flows along to the grave . Keywords : Bridal Apparel Design Talang Mamak Tribe